Lignin degradation of banana stem waste using Streptomyces badius - Nadzirah Nadia, Mohd Razif (2009)
In this project, the ability of Streptomyces badius (S. badius) to degrade lignin in banana stem waste was studied. In order for the lignin degradation to occur fermentation process which involved interaction between S. badius and the banana stem waste was conducted. Based on the growth analysis, fermentation process by S. badius takes only one day and 6 hours in 250 ml medium. As for the lignin analysis content, Klason (72% H2SO4) method was employed. There are 5 major step involved in Klason method which are drying, addition of sulfuric acid, addition of distilled water, filtration, and last but not least is drying and moisture removal step. Lignin content was obtained by weighing the final mass of the banana stem waste sample after the final step in Klason method. Following formula were used to determine the percentage of lignin being degraded in the fermentation process.Based on the result of the experiment, Streptomyces badius was able to degrade lignin contain in banana stem waste as much as 23%.